ASPEK HUKUM JUAL BELI TANAH DI BAWAH TANGAN DAN PENDAFTARAN TANAH YANG BERASAL DARI JUAL BELI DI BAWAH TANGAN - wagirin wagirin wagirin; Teo Christoper Limbong (Ilmu Hukum Prima (IHP), 2018)
This is a library using normative research methods. The research data are most derived from some law sources which were dominantly based on applicable laws and regulations. The registration of the transfer of rights has been based on Article 37 paragraph (1) of Government Regulation Number 27 of 1997 concerning Land Registration. However, Article 37 paragraph (2) in the above mentioned Government Regulation has not even been considered taboo. This phenomenon is made by the writer to reveal that registration can facilitate the acquisition of land rights on the basis of direct agreements that are worth doing. Therefore, the head of the district / city land office is asked to carry out registration for the transfer of the rights. To assess the truth of the agreement made directly, the head of the land office must make a discretion that does not burden the applicant or the public who need services for the acquisition of rights to the land. This agreement must be based on good intentions, so that the agreements made have value. This agreement is made to avoid disputes in the future. Registration of the agreement under the hand must be done selectively so that the implementation is right so that this activity can get legal certainty over the rights to the land. To avoid confusion in the community, the Head of the Distrrict / City Land Office data is requested by the Minister of Agrarian Affairs in the field of spatial planning of the national land agency to make certain regulations.